Systematic literature review: implementation of knowledge sharing by information organizations in Indonesia / Salsabila Fastdiecie, Tamara Adriani Salim and Mad Khir Johari Abdullah Sani - Fastdiecie, Salsabila; Salim, Tamara Adriani; Abdullah Sani, Mad Khir Johari (Faculty of Information Management, 2022)
Along with the development of information technology, the concept and implementation of knowledge sharing began to be discussed in various organizations at various scales. In the 21st century, the success of organizations is very dependent on the knowledge they have and how to utilize the existing knowledge. The purpose of this study is to determine the implementation of knowledge sharing by information organizations in Indonesia. The method used in this research is Systematic Literature Review (SLR) to journal articles published in 2018-2021. There are four Research Question (RQ) determined in this study. The final result obtained from this research is that qualitative research methods are widely used to discuss the process of implementing knowledge sharing by information organizations in Indonesia. The process of implementing knowledge sharing can be done through discussions, learning presentations, lectures, joint studies or FGDs, online talk shows, making videos, and others.